Analisis Penerapan Marger pada Bank Syariah Indonesia - Iqbal Febriansyah (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Corporate Restructuring is a method used by companies with the aim of improving and maximizing the performance of a company, so that the company is able to develop, or at least can adapt to the situation faced. There are 4 (four) forms of corporate restructuring, namely: merger, amalgamation, takeover, and separation of the company. The legal consequences of a merger and amalgamation are the same, namely the transfer of assets and liabilities, the transfer of shareholders of the company and the loss of the legal entity status of a company due to the merger and amalgamation. The merger was carried out by 3 banks which later became Bank Syariah Indonesia (BSI). The merger process has its main source of strength in the form of high asset capital, so that BSI is expected to be able to provide financing services needed by the community